2010
DOI: 10.2478/s11756-010-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase activity against guaiacol, NADH, chlorogenic acid, ferulic acid and coniferyl alcohol in root tips of Lotus japonicus and L. corniculatus grown under low pH and aluminium stress

Abstract: The purpose of this study was to examine the impact of low pH and Al stress on the apoplastic production of H2O2 and POD activity against guaiacol, ferulic acid, coniferyl alcohol, NADH and chlorogenic acid in the root tip (RT) of two cultivars of Lotus corniculatus and the model Lotus japonicus Gifu, with the goal to determine the possible role of POD activity in proton and Al tolerance. Our results suggest that Lotus corniculatus cv. UFRGS is more tolerant to low pH and Al than cv. Draco due to the high POD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Authors concluded that peroxidases act as compensation mechanisms which participate in detoxication of free radicals accumulated after gamma irradiation of seeds. Besides the antioxidant activity peroxidases are also involved in cell expansion influencing cell-wall strengthening (Zelinová et al 2010). More detailed picture about distribution of G-POX isoenzymes isolated from roots grown from LTP treated maize seeds are presented in Fig.…”
Section: Activity Of Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors concluded that peroxidases act as compensation mechanisms which participate in detoxication of free radicals accumulated after gamma irradiation of seeds. Besides the antioxidant activity peroxidases are also involved in cell expansion influencing cell-wall strengthening (Zelinová et al 2010). More detailed picture about distribution of G-POX isoenzymes isolated from roots grown from LTP treated maize seeds are presented in Fig.…”
Section: Activity Of Antioxidant Enzymesmentioning
confidence: 99%
“…These ROS are detoxified by the sequential and simultaneous action of a number of enzymes, including superoxide dismutase (SOD), peroxidase (POX), and catalase (CAT). It's generally known, that the coordinated action of several antioxidant enzymes is activated when plants are exposed to different kinds of stress (Cakmak & Horst 1991;Suzuki & Mittler 2006;Agarwal 2007;Apostolova et al 2008;Zelinová et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After through washing, the fresh roots and leaves, tissues were crushed in 0.1 % trichloroacetic acid 61 with the aid of mortar and pestle and centrifuged for 15 min at 10,000 rpm. The supernatant was then mixed with potassium iodide (1M) and phosphate buffer (10 mM, ph 7.0) and kept for 1 h in the dark.…”
Section: Analysis H 2 O 2 In Plant Tissuesmentioning
confidence: 99%
“…The content of free protein was determined using the Coomassie brilliant blue method (Bradford, 1976), and the activities of POD and SOD enzymes were determined using the guaiacol (Zelinová et al, 2010) and NBT (Rukmini et al, 2004) methods, respectively. The contents of free sugars, amino acids, and polyphenols were measured using the anthrone (Li and Li, 2013), the ninhydrin (Sun et al, 2006), and the Folin phenol (Li et al, 2008) methods, respectively.…”
Section: Determination Of Physiological Indexes Related To Stress Resistancementioning
confidence: 99%